These newcomes : William Makepeace Thackeray and novelistic particularity - Gao, Timothy (2022)
Through a sustained close reading of William Makepeace Thackeray's 1855 novel The Newcomes, this essay examines three analogous types of particularity in the novel: The particularity of loved ones in the social network, of fictional persons in the literary work, and of the individual text. Drawing on recent sociological and network readings of Victorian narrative, I argue that Thackeray's plot about relationships in the marriage market is reflected (on the level of form) by the structural relation between characters and text, and (on the level of the reading experience) by the affective engagement of the reader to the novel. As characters encounter problems in replacing old relations (former lovers, deceased spouses, estranged relatives) with new ones, the novel raises analogous questions about the replaceability of characters as textual constructs or fictional persons, and of the novel itself as one experience among multitudes on offer in the nineteenth-century market. A tension between the continual or particular experience of an individual novel and the felt historical pressure of novels en masse registers in the text itself as a formal and narrative problem, one that leads us suggestively toward recent methodological debates about intimate and distant reading.